Inflation and the Income Share of the Rich: Evidence for 12 OECD Countries - Mehdi el Herradi; Jakob de Haan; Aurélien Leroy (Center for Economic Studies and ifo Institute (CESifo), 2020)
This paper examines the distributional implications of inflation on top income shares in 12 advanced economies using data over the period 1920-2016. We use Local Projections to analyze how top income shares respond to an inflation shock, and panel regressions in which all variables are defined as five-year averages to examine the impact of inflation on the position of the top-one-percent in the long run. Our findings suggest that inflation reduces the share of national income held by the top one percent. Furthermore, we find that inflation shocks and long-run inflation have similar effects on top income shares.
Keywords: D63; E50; E52; 330; inflation; inequality; top income shares; income distribution